Analisis Faktor-faktor yang Mempengaruhi Pengembangan Karier Karyawan Perbankan di Kota Makassar - Muis, Mahlia (Jurnal Aplikasi Manajemen, 2009)
The aim of the study was to analyze the effect of promotion, education, working time, sex, martial status, number of children, horizontal movement, and number of reward on career development of bank's staff in Makassar municipal government and the most dominant factor affecting the career development. The analysis used in the study was descriptive analysis and logistic regression. There is a positive and significant correlation between education, sex, number of reward on career development, and there is insignificant correlation between age, working time, marital status, number of children and moving horizontal on career development.